2007
DOI: 10.1037/0021-9010.92.3.693
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and genetic determinants of leadership role occupancy among women.

Abstract: The genetic and developmental influences on leadership role occupancy were investigated using a sample of 178 fraternal and 214 identical female twins. Two general developmental factors were identified, one involving formal work experiences and the other a family experiences factor hypothesized to influence whether women move into positions of leadership in organizations. Results indicated that 32% of the variance in leadership role occupancy was associated with heritability. The 2 developmental factors also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
146
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(162 citation statements)
references
References 59 publications
(58 reference statements)
7
146
1
Order By: Relevance
“…The authors found that for 238 male identical twin pairs and 188 fraternal twin pairs reared together, the proportion of variance due to genetic influences on the leadership role occupancy scale was 0.30. Similar findings were found in a study using 89 fraternal and 107 identical female twin pairs conducted by Arvey, Zhang, Avolio, and Krueger (2007). These results indicated that around 70% of the variance in leadership emergence and effectiveness could be attributed to non-genetic factors, namely developmental experiences.…”
Section: Assessment Andsupporting
confidence: 76%
“…The authors found that for 238 male identical twin pairs and 188 fraternal twin pairs reared together, the proportion of variance due to genetic influences on the leadership role occupancy scale was 0.30. Similar findings were found in a study using 89 fraternal and 107 identical female twin pairs conducted by Arvey, Zhang, Avolio, and Krueger (2007). These results indicated that around 70% of the variance in leadership emergence and effectiveness could be attributed to non-genetic factors, namely developmental experiences.…”
Section: Assessment Andsupporting
confidence: 76%
“…1841). The possible role of genetics in the «born leader» remains a popular topic today among lay people and scholars alike (Arvey, Rotundo, Johnson, Zhang, & McGue, 2006;Arvey, Zhang, Avolio, & Krueger, 2007 ;Chaturvedi, Zyphur, Arvey, Avolio, & Larsson, 2012). One of the notable differences between a «hero» and a «good leader» is the expectation that a «hero» is created predominantly by innate factors, whereas education seems more important for the good leader.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded in a meta-analysis study on leadership development programs that the programs had a positive effect of 66% and it was stated that positive outcomes were observed in the cognitive, affective or behavioral areas (Avolio, Reichard, Hannah, Walumbwa and Chan, 2009). It is indicated that while approximately 30% of change is attributed to some genetic factors in the emergence of leadership roles, 70% is required to be explained by non-genetic factors (Arvey, Zhang, Avolio and Krueger, 2007).…”
Section: Discussionmentioning
confidence: 99%